The Axon–Dendrite Targeting of Kv3 (Shaw) Channels Is Determined by a Targeting Motif That Associates with the T1 Domain and Ankyrin G - Xu, Mingxuan (J Neurosci, 2007)
Kv3 (Shaw) channels regulate rapid spiking, transmitter release and dendritic integration of many central neurons. Crucial to functional diversity are the complex targeting patterns of channel proteins. However, the targeting mechanisms are not known. Here we report that the axon–dendrite targeting of Kv3.1 is controlled by a conditional interaction of a C-terminal axonal targeting motif (ATM) with the N-terminal T1 domain and adaptor protein ankyrin G. In cultured hippocampal neurons, although the two splice variants of Kv3.1, Kv3.1a and Kv3.1b, are differentially targeted to the somatodendritic and axonal membrane, respectively, the lysine-rich ATM is surprisingly common for both splice variants. The ATM not only directly binds to the T1 domain in a Zn(2+)-dependent manner, but also associates with the ankyrin-repeat domain of ankyrin G. However, the full-length channel proteins of Kv3.1b display stronger association to ankyrin G than those of Kv3.1a, suggesting that the unique splice domain at Kv3.1b C terminus influences ATM binding to T1 and ankyrin G. Because ankyrin G mainly resides at the axon initial segment, we propose that it may function as a barrier for axon–dendrite targeting of Kv3.1 channels. In support of this idea, disrupting ankyrin G function either by over-expressing a dominant-negative mutant or by siRNA knockdown decreases polarized axon–dendrite targeting of both Kv3.1a and Kv3.1b. We conclude that the conditional ATM masked by the T1 domain in Kv3.1a is exposed by the splice domain in Kv3.1b, and is subsequently recognized by ankyrin G to target Kv3.1b into the axon.